1987
DOI: 10.1017/s0373463300000631
|View full text |Cite
|
Sign up to set email alerts
|

Navigational Ideas and the Yorkshire Ripper Investigation

Abstract: This paper describes the application of navigational ideas during a late stage of the Yorkshire Ripper investigation. The conclusions reached were irrevocably recorded before the ultimate facts were established by the arrest and conviction of the killer. The reader is invited to assess the degree of success of the method and to rework the data supplied according to his own navigational ideas. The suggestion is made that navigational concepts may become a valuable weapon in the field of crime investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Many studies have shown that offenders usually do not travel very far from home to commit crimes (White, 1932;Pyle, 1974;Repetto, 1974;Curtis 1974;Kind, 1987). Shaw and McKay illustrated this general trend as long ago as 1942 in their Chicago studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that offenders usually do not travel very far from home to commit crimes (White, 1932;Pyle, 1974;Repetto, 1974;Curtis 1974;Kind, 1987). Shaw and McKay illustrated this general trend as long ago as 1942 in their Chicago studies.…”
Section: Introductionmentioning
confidence: 99%
“…They established that there is a limited area of zones in which offenders will offend and that these zones were geographically close to the zones in which the offenders lived. However the majority of the research undertaken to date has involved case studies of, for example, classic crime series like 'the Yorkshire Ripper' (Kind, 1987). Alternatively they have considered the aggregate pattern of the spatial activity of a sample of criminals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These calculations are done on the X and Y axis of the coordinates. The first application of this type of techniques was in the case of the Yorkshire Ripper, England, in the year 1987, when the mean center was used to determine the homicide's place of residence [23]. Although it did not take such statistical results into account during the police investigation, it showed an approach which was accurate enough when the aggressor was arrested.…”
Section: Geographical Profiling Techniquesmentioning
confidence: 99%
“…For the present study the focus is on the place of residence, which is referred to as the home. Kind (1987) was one of the first forensic scientists to show the direct application of geographical models, such as those studied here, to an ongoing criminal investigation in his pioneering exploration of the location of the offenses of the "Yorkshire Ripper." He showed that a "center of gravity" to the Ripper's crime locations, or as might be termed from geography a "centroid," accurately indicated where the offender was eventually found to live.…”
Section: Investigative Geographymentioning
confidence: 99%
“…The 13-values for any location is the mean of the values assigned to that location by the calibrated function radially assigned to each crime location within the series. This process is an extension of Kind's (1987) work in that, rather than producing a single point as an indication of the offender's residence, a more comprehensive prioritized map is produced. It is also more detailed than the system studied by Canter and Gregory .…”
Section: Application Of the Functionmentioning
confidence: 99%